Internalizing Huma Betang into Civic Education for National Character Building - Triyani; Dian Nastiti; Mariyani; Devi Sutrisno Putri; Syahrul (IAIN Palangka Raya, 2026)
The development of Indonesian society has shown increasingly complex social dynamics, marked by increasing social fragmentation, intolerance, weakening communal solidarity, and a decline in the quality of civic participation, especially among the younger generation. Huma Betang philosophy is a local wisdom that lives in Bumi Tambun Bungai, Central Kalimantan. Huma Betang philosophy has noble values that can be used as a reference in living the life of society and the state, such as togetherness, honesty, equality, and tolerance. The values of the Huma Betang philosophy follow the values developed in Civic Education. The research aimed to address the challenges of character crisis, strengthen social cohesion, and emphasize the role of Civic Education as the primary vehicle for forming a national character rooted in local wisdom and oriented towards the nation's future. The study used a qualitative approach to explore the Huma Betang philosophy's values in developing national character education. Data were collected using interviews, documentation, and literature reviews, and subsequently analyzed with descriptive qualitative techniques. Source triangulation was used to ensure data validity. The Huma Betang philosophy, as a crystallization of Central Kalimantan's local values, serves as a crucial foundation for national character building. Through this character development, Indonesian citizens are expected to embody and practice these national cultural values in their social and civic lives.